The model of ontological reflection of ecological and economic value orientations formation in the process of vocational education - A. A. Salamatov; D. S. Gordeeva (Образование и наука)
Introduction. In modern Russia, the environmental problems affected all developing countries are growing and the postponement of these problems could lead to economic collapse. The fundamental transformation of social and economic institutions is necessary to avoid environmental degradation. Primarily, science requires a transition to a paradigm, which integrates economic well-being and environmental security of current and future generations. The translator of such synthesis can and should be a vocational training system.The aim of the present article is to demonstrate and justify the model of ecological and economic value orientations formation in vocational education members; since this model ensures integrity, systemacity, continuity of work and parity of actions of all participants in the educational process.Methodology and research methods. The design of the model was based on holistic, synergistic and professiographic approaches. The principles of personal targeting, self-reflection, ecosinergism and continuity were applied. Reflexive analysis was the leading method in the research.Results and scientific novelty. The authors give the definition of ecological and economic value orientations, considering them as formations in the structure of individual consciousness, which are subjective ideal samples and objective bases of responsible ecological and economic activity of the individual, social institutions and production enterprises. However, the formation and development of such orientations in the vocational education system is very difficult without the certain economic order to train specialists in order to make cost-effective and moral focused on environmental issues. Today’s graduates of non-ecological specialties have superficial ideas of the nature and its relationship with the state of society and they are practically unaware of the basics of environmental management and ecological-economic risks. In recent decades, the gap between education and scientific achievements has become increasingly obvious in the field of genetic engineering, cyber production, autotrophic and chemical-biological technologies with the use of artificially grown living systems, etc., which change initial ideas about ecology and can raise civilisation to a new level of evolution. It is necessary not only to transmit the latest discoveries and ecological knowledge to students, but also to try to change their world view by instilling ecocentric morality. In this regard, the model for ontological reflection of ecological and economic values formation has been developed. This model emphasises that professional readiness in the modern world is determined not only by a set of certain competencies, but also by the ability to analyse the whole set of external externalities to prevent environmental threats, without losing the economic benefit of activities.Practical significance. The authors believe that the introduction of a reflexive model into educational practice could be applied to train highly qualified specialists with a full range of professional competencies, value orientations and personal qualities, which correspond to the realities of unstable ecological and economic state of society.